Threat of platform-owner entry and complementor responses - Wen, Wen; Zhu, Feng (Strategic Management Journal, 2019)
[Research Summary:This paper studies the impact of platform-owner entry threat on complementors in platform-based markets. We examine how app developers on the Android mobile platform adjust innovation efforts (rate and direction) and value-capture strategies in response to the threat of Google's entry into their markets. We find that after Google's entry threat increases, affected developers reduce innovation and raise the prices for the affected apps. However, their incentives to innovate are not completely suppressed; rather, they shift innovation to unaffected and new apps. Given that many apps already offer similar features, Google's entry threat may thus reduce wasteful development efforts. We discuss the implications of these results for platform owners, complementors, and policy makers. Managerial Summary:We examine one prevalent source of conflict: platform owners' entry into complementary product spaces. We show that app developers on Google's Android system are strategic and nimble actors. They respond to the threat of Google's entry by adjusting both value-creation and value-capture strategies. We also show that platform owners could use direct entry to shape innovation directions and encourage variety of complements. Overall, on the one hand, Google's entry may have pushed complementors into other areas (which might be less lucrative) and strengthened its position in the mobile market. On the other hand, the entry may have reduced wasteful production efforts in the development of redundant applications. The overall welfare implication is thus ambiguous.]